1983
DOI: 10.1080/00288233.1983.10420949
|View full text |Cite
|
Sign up to set email alerts
|

Naturalised subterranean clover in New Zealand

Abstract: Subterranean clover seed was collected from 51 old pastures in 9 regions of New Zealand. Spaced plants from these 51 populations were grown at Palmerston North and compared with a range of Australian commercial lines. Mt Barker types were present in every New Zealand population sampled and constituted 74% of the total collection. Tallarook and Woogenellup made up 21% and 2070 of the collection respectively. A very late-flowering dwarf type with Mt

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Williams et al (1990) concluded that most pastures in summer-dry hill pastures contained low proportions of white (Trifolium repens l.) and subterraneum (T. subterraneum l.) clovers. This was associated with considerable variability in distribution related to such factors as drought, soil fertility, grazing intensity and frequency and temperature at contrasting sites (Suckling et al 1983;macFarlane & Sheath 1984). Gillingham et al (2003a) suggested that as a result of this variability in clover content, which was also related to slope and aspect, a differential N and P fertiliser application strategy on a range of hill pastures could result in higher overall pasture productivity, than from the use of P fertiliser alone.…”
Section: Introductionmentioning
confidence: 99%
“…Williams et al (1990) concluded that most pastures in summer-dry hill pastures contained low proportions of white (Trifolium repens l.) and subterraneum (T. subterraneum l.) clovers. This was associated with considerable variability in distribution related to such factors as drought, soil fertility, grazing intensity and frequency and temperature at contrasting sites (Suckling et al 1983;macFarlane & Sheath 1984). Gillingham et al (2003a) suggested that as a result of this variability in clover content, which was also related to slope and aspect, a differential N and P fertiliser application strategy on a range of hill pastures could result in higher overall pasture productivity, than from the use of P fertiliser alone.…”
Section: Introductionmentioning
confidence: 99%
“…Relative peak flowering times and maturity rankings were as expected (Scott 1972;Cocks & Phillips 1979;Suckling et al 1983). Whereas the long-term compatability of floweringheseeding time and moisture availability can only be tested over several years, the flexibility and desirability of extended flowering times and intensities as exhibited by Bacchus Marsh and Mt Barker should be recognised.…”
Section: Resultsmentioning
confidence: 99%
“…At Ballantrae, 'Mt Barker' flowered only 6-9 days before 'Tallarook' , instead of an expected interval of 20--26 days (Suckling et al 1983;Collins et al 1984). Later than expected flowering of 'Mt Barker' was also recorded at Whatawhata in 1982 (Sheath & Macfarlane 1990b) whereas at other sites, such as Kaikohe (Rumball & Cooper 1990) the flowering date of 'Mt Barker' was more in line with expectations.…”
Section: Discussionmentioning
confidence: 99%